A qualitative examination of college students' perceptions of cannabis: insights into the normalization of cannabis use on a college campus. Issue 3 (3rd April 2022) - Kilwein, Tess M.; Wedell, Emma; Herchenroeder, Luke; Bravo, Adrian J.; Looby, Alison
Abstract: Objective This study aimed to qualitatively examine how perceptions of cannabis differ among college students in an effort to better understand the changing landscape of cannabis on college campuses. Participants: Forty-six predominantly male (69.9%; M age = 23.15, SD  = 4.11) college students attending a border state university (i.e., a state that has not yet legalized cannabis but borders a state that has). Methods: Participants engaged in facilitated focus group discussions ( N  = 5) about cannabis-related issues. Results: Thematic analysis uncovered three primary themes and six subthemes. Main themes included: 1) User Heterogeneity and Identity, 2) Relative Benefits and Harms of Cannabis, and 3) Social Position of Cannabis on Campus Culture. Conclusions: Cannabis has quickly integrated into the college social environment, with social stigmatization and identification with cannabis impacting decisions to use. Findings inform existing college health programs on how to approach conversations about cannabis with students.